Prioritas Penanganan Jalan Nasional Dengan Menggunakan Metode Ahp Dan Anp: Ruas Jalan Bts. Tapteng/Tapsel – Batang Toru – Bts. Kota Sidempuan - T. Rahmatsyah Putra; Ahmad Perwira Mulia Tarigan; Gina Cynthia Raphita Hasibuan (Syntax Idea, 2022)
The government's limited budget in managing the condition of the road pavement causes the government to compile a priority ranking of the roads to be handled. Each decision maker has a different assessment for each factor or criterion that is considered in determining the path. This problem requires the same perception from decision makers in choosing road handling priorities. Priority by determining more than one criteria can be done using Multi Criteria Decision Making (MCDM) analysis such as Analytic Hierarchy Process (AHP) and Analytic Network Process (ANP). This study seeks to obtain priority handling of the Jalan Bts. Tapteng/Tapsel – Batang Toru – Bts. Sidempuan City using AHP and ANP methods. The criteria used are traffic volume, level of road damage, government policies, handling costs, and area development. The segmentation of the road segment is applied in this study into 9 sub-sections to obtain a uniform alternative length of the road. The results show that the most influential criteria in road handling using the AHP method are traffic volume (0.428), followed by policy (0.192), cost (0.187), road conditions (0.141), and area development (0.052). While in the ANP method, the criteria with the largest weight are traffic volume (0.301), followed by policies (0.196), costs (0.194), road conditions (0.174), and area development (0.134). The results of the two methods also determine the priority of different road handling roads. The results of the ANP method are expected to be a more objective priority due to the consideration of feedback on the elements and clusters themselves.